Predicted future changes in ocean temperature and pH do not affect prey selection by the girdled dogwhelk Trochia cingulata. Issue 1 (2nd January 2022) - Martin, N; Clusella-Trullas, S; Robinson, TB
Abstract : Predator–prey relationships can drive community dynamics in marine systems, but it remains unclear how future changes in seawater temperatures and pH will influence these relationships. This study assessed the effect of predicted future temperatures and pH on the prey choice of the girdled dogwhelk Trochia cingulata (family Muricidae) when offered native ( Aulacomya atra, Choromytilus meridionalis ) and alien ( Semimytilus algosus ) mussels. Whelks were exposed to three pH levels: 8.0 (current), 7.7 (intermediate) and 7.5 (extreme), at each of three temperatures: 9 °C (cooling), 13 °C (current) and 17 °C (warming) for 6 weeks. Thereafter, the prey preference and predation rate were compared among treatments. Within two weeks, 98% of whelks exposed to warming died, precluding assessment of how warming affects their prey preference. Despite high mortality, the highest predation rates were recorded at 17 °C regardless of the pH level, likely reflecting increased energy costs and ingestion rates associated with warming. In the remaining treatments whelks preferred S. algosus irrespective of the levels of seawater cooling or acidification. These results align with previous work that demonstrated a preference by T. cingulata for S. algosus and suggest that the predator–prey relationship between this whelk and its mussel prey is unlikely to be disrupted under future marine conditions.